ANALISIS REGRESI LOGISTIK DALAM PENENTUAN MODEL BERAT BADAN BAYI LAHIR - I GUSTI AYU MADE SRINADI (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2007)
Infant weight at Birth (BBBL) is one standard of The Healthy Program with expectation isthe Normal In-fant Weight at Birth (³ 2,5 kg). The factors which influence to BBBL are weight,height, parities, ages, hae-moglobin pencentage, blood pressure and education of mother’s.This study want to know which factors have major probability and how are the form of the factorsto the BBBL.Data used in this research are mother’s data whom give delivery in Govermant Hospital,delivery clinic or delivery nurse’s.Mother’s characteristic shown in data descriptive analysis. Single logistic regression detecteach potential variable to construct the multiple logistic regression model. The variables used forconstruct the multiple logis-tic regression model have significant contribution to the BBBL, thebest model is : P =+ + + + -Model above showed mother’s education and mother’s activities influences to the BBBL.Odds ratio values for every factors which influenced to the BBBL ³ 2,5 kg compared withBBBL < 2,5 kg find for mother’s education (junior high school, senior high school and the degreeof university) with proba-bility 2,6414, 22,2936 and 50,5504 times higher than mother’seducation for elementary school background.